Massive tramadol ingestion resulting in fatal brain injury – a pharmacokinetic study with discussion on the involved mechanisms of toxicity. (2nd September 2022) - Puszkiel, Alicja; Malissin, Isabelle; Cisternino, Salvatore; Pallet, Nicolas; Declèves, Xavier; Mégarbane, Bruno
Abstract: Background: Tramadol-attributed toxicity may involve opioid-like, serotoninergic, and noradrenergic mechanisms. We investigated the mechanisms of toxicity in a massive tramadol ingestion case by examining serial clinical, imaging, electroencephalography, pharmacokinetics, and genotyping data. Case report: A 32-year-old female who presumably ingested 9000 mg sustained-release tramadol was found comatose without hypoglycemia, bradypnea, hypotension, marked hypoxemia or seizures. She developed eyelid myoclonus and non-reactive mydriasis. Electroencephalogram showed non-reactive encephalopathy. MRI showed extensive brain injury. Despite supportive care and ventricular derivation, brain death occurred on day 12. Methods: Plasma concentrations of tramadol and metabolites were measured using a liquid chromatography–tandem mass spectrometry assay. Genotyping for the presence of metabolizing cytochrome P450 (CYP) gene polymorphisms was performed. Results: Plasma concentrations of tramadol and metabolites were extremely high (∼70-fold the therapeutic concentrations) and slowly decreased during the first ∼146 h post-admission, possibly due to prolonged gastrointestinal absorption. Elimination half-lives were 2–3-fold longer than usual values. The patient was an intermediate CYP2D6 metabolizer with decreased CYP3A4 and CYP2B6 activities. Clinical and electroencephalographic data did not support the hypotheses of opioid or serotoninergic toxicity nor prolonged/repeated seizures. Based on serial imaging showing progressive extension of ischemic edema in the context of prolonged high plasma concentrations, we hypothesized a cerebral vasospasm as mechanism of injury. Conclusion: Massive tramadol ingestion with prolonged high plasma concentrations can result in severe brain injury, possibly involving vasospasm.